Epidemiology, molecular characterisation and tropism of the Hepatitis G Virus / GBV-C - Tucker, Timothy Johan Paul (Division of Virology, 2017)
The hepatitis G virus and GBV-C are recently discovered variants of the same virus belonging to the family Flavivirus (HGV/GBV-C). Although initially thought to be a hepatitis virus, it has been shown to have no association with liver disease. No work has been performed on the prevalence or molecular characteristics of HGV/GBV-C in southern Africa. In addition, although it is clear that the liver is not the primary site of replication, there is no data on the sites of HGV/GBV-C replication in normal subjects. Thus, this study aimed to assess the prevalence of HGV/GBV-C carriage in the urban and rural adult Black communities of the Western and Eastern Cape Provinces of South Africa, and compare it to the prevalence of serological markers of the hepatitis viruses A-E. In addition, this study aimed to assess the molecular features of South African HGV/GBV-C isolates and demonstrate the organs where viral replication was present. The mean prevalences of antibodies to hepatitis A lgG, hepatitis B surface antigen and antibodies to hepatitis B surface antigen were 98%, 4.3% and 61.1 % respectively. The mean prevalence of antibodies to hepatitis C was 1.8%. No significant differences in prevalence were shown between the urban and rural regions for these viruses. The mean anti-hepatitis E prevalence varied from 5.8% to 19.1 % in the different regions. Those living in mud houses without access to chlorinated tap water had a significantly higher prevalence of antihepatitis E. No anti-hepatitis D positive samples were isolated. The overall prevalence of HGV/GBV-C was 26.9%, with rural communities having a significantly lower prevalence than urban communities. A significant relationship was observed between HGV/GBV-C infection with the use of illicit drugs, female gender, younger age and past blood transfusions. Phylogenetic analysis demonstrated a novel fourth South African HGV/GBV-C genotype, distinct from the previously described genotypes 1-3. In addition, certain isolates showed a major deletion in the highly conserved 5' non-coding region of HGV/GBV-C. Analysis of 23 tissue biopsies from infected cadavers suggested that the spleen and bone marrow were the primary sites of HGV/GBVC replication.